Penggunaan Metode Pembelajaran Talking Stick dalam Meningkatkan Hasil Belajar IPA - Ari Aprilia Dwiana; Ramdhan Witarsa; Molli Wahyuni (Journal on Education, 2022)
This study aims to describe the application of the stick-taking learning method to style material to improve student learning outcomes in class IV SD Pahlawan. The formulation of the problem in this study is how is the process of applying the Talking Stick learning method to style material to improve the learning outcomes of fourth grade students at Pahlawan Elementary School for the 2021/2022 academic year and how are student learning outcomes by applying the Talking Stick method to science subjects in style material for fourth grade students at SD Pahlawan . This research was conducted in class IV SD Pahlawan. This research was conducted from March to April 2021 which consisted of two cycles. The object of this study were 25 grade IV students, with 12 boys and 13 girls. The techniques used in this research are quantitative data analysis techniques and qualitative data analysis techniques. Based on the results of the study it can be concluded that in cycle I it is still classified as incomplete with an average of 63.80. Furthermore, out of 25 students, only 11 students were declared complete, achieving a percentage of 44% individually. Meanwhile, the learning outcomes of students in cycle II were quite good because they had achieved an average of 72.00 and out of 25 students there were 21 students who passed with an average of 84% who achieved completeness in this way. Thus, it can be concluded that applying the Talking Stick method to style material can improve the learning outcomes of fourth grade students at SD Pahlawan.